A Study on the Journey of Transformation from a Traditional Platform to Online Teaching Practices at Higher Education Institutions - Akhtar, Samina; Khurshid, Khalid (Annals of Human and Social Sciences, 2023)
The widespread usage of digital technology has placed pressure on academic institutions to rethink their approaches to learning and instruction in contemporary times. The fundamental objective of this investigation was to explore departmental heads' perspectives on online teaching practices at HEI (Higher Education Institutions). Secondly, to suggest some suitable initiatives for the best online teaching practices at HEI. This investigation was qualitative in nature. For this study, five (5) HEIs in South Punjab, Pakistan, were chosen. To obtain qualitative data, a semi-structured interview was arranged for a sample of eighteen (18) heads/chairpersons selected by convenient sampling. The data was analyzed using NVIVO 12 for a comprehensive thematic analysis. This qualitative research unearthed a number of issues associated with the transformation towards online learning practices. Furthermore, it revealed the initiatives presented by the departmental heads to address the issues and the requirement of providing further training for teachers to improve their potential.